Identification of internally sialylated carbohydrate tumor marker candidates, including Sda/CAD antigens, by focused glycomic analyses utilizing the substrate specificity of neuraminidase - Tanaka-Okamoto, Miki; Hanzawa, Ken; Mukai, Mikio; Takahashi, Hidenori; Ohue, Masayuki; Miyamoto, Yasuhide (Glycobiology (Oxford), 2018)
In our previous study, 14 sulfated carbohydrate tumor marker candidates were identified by focused glycomic analyses. Here, glycomic analyses focused on internally sialylated glycans to identify novel marker candidates. Internally sialylated glycans were enriched by digestion of pyridylaminated glycans prepared from sera with α-neuraminidase from Salmonella typhimurium, which did not cleave sialic acids linked to internal residues, followed by anion-exchange chromatography. Next, internally sialylated O-glycan profiles were constructed using two types of high performance liquid chromatography, which were compared between 20 healthy controls and 11 patients with gastric cancer and 9 patients with pancreatic cancer. In all, 17 marker candidates were identified. The structures of glycan candidates were precisely analyzed using enzymatic digestion, glycan synthesis, 2D mapping and mass spectrometry. Among 17 candidates, one was STn, and the other 16 comprised 10 core1, 1 core2 and 5 core3 glycans. The various structures included a α2,6-sialylated reducing terminal GalNAc and α2,6-sialylated type1 N-acetyl-lactosamine. Eight candidates possessed the Sda/CAD antigen. The levels of these candidate glycans in sera from all 40 subjects were quantified using a selected reaction monitoring assay and found to be elevated in at least one or more patients. Although the serum levels of each candidate glycan varied between patients, those candidates having the same backbone or determinant, such as core3 backbone and core1 structures with extended type1 N-acetyl-lactosamine, displayed similar patterns of elevation. These results suggest that analysis of multiple markers may be an effective means of diagnosing various cancers.